PEMBENTUKAN SENTRA INDUSTRI UNTUK MENGEMBANGKAN USAHA KERAJINAN TOPENG BARONGAN DHADAK MERAK REYOG DENGAN PENDEKATAN ONE VILLAGE ONE PRODUCT DI KABUPATEN PONOROGO - Nugrahini, Dwi Setya; Santoso, Sigit; Riyanto, Guntur (Jurnal Pendidikan Insan Mandiri, 2016)
The objectives of research: (1) to find out the establishment of industrial center to develop Barongan Dhadak Merak Reyog Mask Handicraft Business with One Village One Product approach in Ponorogo Regency, (2) to find out the implementation of entrepreneurship education for the crafters to develop Barongan Dhadak Merak Reyog Mask Handicraft industry in Ponorogo Regency. The method employed was qualitative one. The data sources employed were informant, archive and document, place, event and activity. Techniques of collecting data used were in-depth interview, observation, and document and archive recording, with purposive snowball sampling technique. Data validation was carried out using data source and method triangulations. Technique of analyzing data used was interactive model including: data reduction, data display and conclusion drawing or verification. This study concluded that: (1) the establishment of industrial center to develop Barongan Dhadak Merak Reyog Mask Handicraft Business with One Village One Product approach was conducted by uniting the stakeholders involved in OVOP approach to Barongan Dhadak Merak Reyog Mask Handicraft industry in Ponorogo Regency, including academicians/educators (A), businessman (businessperson/employer crafter) (B), government (G), and (2) the implementation of entrepreneurship education was still in adequate for the crafters in Barongan Dhadak Merak Reyog Mask Handicraft industry in Ponorogo Regency because this education only focused on skill and training.Keywords: Industrial Center Establishment, Developing Business , One Village One Product approach.